2002
DOI: 10.1097/01.asn.0000015616.97847.0c
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Blocks Enhanced Paracellular Backflux in Proximal Tubules

Abstract: Abstract. Renal interstitial hydrostatic pressure (RIHP) is a link between increased arterial BP and natriuresis. The mechanism whereby increases in RIHP inhibits sodium and water transport across the mammalian proximal tubule epithelium may involve changes in flux across the tight junction of the proximal tubule. The purpose of this study was to determine the effects of increases in RIHP and inhibition of cyclooxygenase on paracellular backflux of an extracellular marker from the renal interstitium into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The PGE 2 was believed to derive from endothelial cells of the preglomerular vasculature and, during increased RIHP, to inhibit proximal tubular Na ϩ reabsorption (486,509,536,538,790,797,823,1207). The mechanism may involve PGE 2 -induced enhancement of paracellular Na ϩ backflux from the interstitium into the tubular lumen during increased RIHP that would decrease net Na ϩ reabsorption (1207).…”
Section: (Figure 4 a And B)mentioning
confidence: 99%
“…The PGE 2 was believed to derive from endothelial cells of the preglomerular vasculature and, during increased RIHP, to inhibit proximal tubular Na ϩ reabsorption (486,509,536,538,790,797,823,1207). The mechanism may involve PGE 2 -induced enhancement of paracellular Na ϩ backflux from the interstitium into the tubular lumen during increased RIHP that would decrease net Na ϩ reabsorption (1207).…”
Section: (Figure 4 a And B)mentioning
confidence: 99%
“…The effector mechanisms that connect medullary perfusion to regulation of epithelial sodium transport are not well established, but various possibilities exist. It has been demonstrated that increases in perfusion pressure cause a secondary increase in renal interstitial pressure and that the latter leads to inhibition of proximal reabsorption (128). Some forms of hypertension are associated with regulation of sodium transport pathways (71), but this would not account for the immediate ability of increased perfusion pressure to cause saliuresis.…”
Section: Role Of Dvr In Regulation Of Medullary Blood Flowmentioning
confidence: 99%
“…In addition to active sodium transport, passive diffusion of NaCl through paracellular pathways contributes to renal interstitial hydrostatic pressure (RIHP) and may affect pressure natriuresis [7]. Ramsey et al demonstrated that increased RIHP enhances paracellular backflux from the renal interstitium to the tubular lumen through the intercellular TJs [8]. …”
Section: Introductionmentioning
confidence: 99%